TECHNICAL IMPLEMENTATION OF WATER LOSS ACCOUNTING IN MUNICIPAL WATER SUPPLY SYSTEMS - Матиборський, В. В.; Смирнитська, М. Б. (Proceedings of National Aviation University (archive), 2021)
The analysis of operation of water flow measuring devices at different stages of processing and use is carried out. The possibility of using an electric flow meter to account for water losses in urban water supply and sewerage systems is shown.